GONÇALVES DIAS E A SEÇÃO ETNOGRÁFICA E NARRATIVA DA COMISSÃO CIENTÍFICA DE EXPLORAÇÃO (1859-1861) - EDUARDO HENRIQUE BARBOSA DE VASCONCELOS (Espaço Ameríndio, 2012)
Brazil should be known and studied by the Brazilians. This idea was the force that justified the constitution of the Comissão Científica de Exploração (CCE), founded by members of the Brazilian Historic and Geographic Institute and supported by the Brazilian imperial government, in order to motivate research on the “young” country. Within this ambitious scientific and political project, ethnographic knowledge and practices were embraced in the deeds assigned to the scientist and poet Gonçalves Dias, chief of the section of ethnography and travel narrative, whom should have performed his activities in Ceará province throughout 3 years (1859-1961). To reflect on the deeds of the mentioned section during its execution is the goal of this paper.O Brasil deve ser conhecido e estudado pelos brasileiros. Essa ideia foi a força que gestou e legitimou a criação da Comissão Cientifica Exploração (CCE), criada pelos membros do Instituto Histórico e Geográfico Brasileiro com o apoio e o financiamento do governo imperial brasileiro para estimular as pesquisas sobre o “jovem” país. Dentro desse audacioso plano político-científico, o saber e o fazer etnográficos também se fizeram presentes nas ações atribuídas ao poeta/cientista Gonçalves Dias, chefe-responsável das atividades da seção etnográfica e narrativa da CCE e que deveria ter desenvolvido suas atividades na província do Ceará durante 03 anos (1859-1861). Pensar as ações da seção etnográfica e narrativa durante o período de atuação na província cearense é o objetivo deste trabalho.